Biocomposite microfibrous/hydrogel scaffold containing sulfated alginate hydrogel for acceleration of chondrogenic differentiation - Nafiseh Bahrami; Seyed Mohammad Amin Haramshahi; Seyed Amirhesam Jamali; Mahdi Saeed; Mohamad Pezeshki-Modaress (Materials & Design, 2025)
In the present research, a fiber/hydrogel biocomposite scaffold consisting of alginate sulfate-modified polycaprolactone fibers and alginate sulfate/gelatin hydrogel was fabricated and its potential as a cartilage scaffold was evaluated. PCL fibers were prepared using centrifugal spinning and functionalized with alginate sulfate chains. Then, to integrate the fibers and construct the composite scaffold, these fibers were mixed with different hydrogel binders including alginate sulfate, gelatin and a combination of both. The analyses performed on the composite scaffolds showed that the porosity of the scaffolds was above 90 %, and their swelling was above 700 %. The compressive modulus of the scaffolds in the dry and wet states was in the range of 16–70 and 4–8 kPa, respectively. In the wet state, the compressive modulus of the scaffold with AS/GL binder increased by 133 and 11 % compared to the scaffolds with AS and GL, respectively. According to cell culture studies, the cell viability of the scaffolds was above 80 %, corroborating their nontoxic nature. In addition, cell adhesion and migration were higher in the scaffolds with GL and AS/GL binders than in the scaffold with AS binder. The expression of cartilage related genes, namely SOX9, COLL II and AGG, in the scaffold with AS/GL binder was 1.4, 3.3 and 4.6 times that of the scaffold with AS binder and 4.8, 8.2 and 8.2 times that of the scaffold with GL binder, respectively. The scaffold with AS/GL binder has great potential for cartilage regeneration by having a higher compressive modulus and providing better chondrogenic differentiation.